1998
DOI: 10.1109/36.718858
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wideband SAR interferometry

Abstract: We introduce ultra-wideband synthetic aperture radar (SAR) interferometry as a new technique for topographic height retrieval. It is based on using a SAR system with large relative bandwidth that acquires data along two parallel tracks with a separation of the same order of magnitude as the flight altitude. The complex SAR image data are resampled onto a common reference surface, filtered, and followed by a Hermitian multiplication. The resulting interferogram is shown to have a finite depth-of-focus (DOF) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 21 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…This is a prerequisite for improving geocoding, correctly calculating the correct projection factor, and for studying effects of ground slopes. In [22], Ulander and Frölind concluded that ultra-wideband SAR interferometry, using the CARABAS-II sensor, has a potential for automated and rapid high spatial resolution, wide-area topographic mapping.…”
Section: Discussionmentioning
confidence: 99%
“…This is a prerequisite for improving geocoding, correctly calculating the correct projection factor, and for studying effects of ground slopes. In [22], Ulander and Frölind concluded that ultra-wideband SAR interferometry, using the CARABAS-II sensor, has a potential for automated and rapid high spatial resolution, wide-area topographic mapping.…”
Section: Discussionmentioning
confidence: 99%
“…However, polarimetry deals with the vector nature of the electromagnetic waves, and its strength resides in the physical meaning of the observables 2 . Furthermore, interferometry brings with it range ambiguities that limit its usefulness 3 . The application of polarimetry to SAR interferometry has demonstrated the possibility of optimizing the coherence.…”
Section: Methodologies and Experimental Systemmentioning
confidence: 99%
“…Therefore, radar requirements and performance are driven by the geometry and not by the pattern. Due to the asteroid's small dimension, range and Doppler are not separable and full-SAR processing including range compensation is required, as for Ultra-Wide Band (UWB) radar (Ulander and Frolind, 1998). In this geometry, the performance will vary with the latitude and the longitude on the asteroid surface (resolution, sensitivity, ambiguity ratios, etc.…”
Section: -1 Synthetic Aperture Radar For Small Bodiesmentioning
confidence: 99%